Four mallet marimba playing: a musical approach for all levels - Zeltsman, Nancy. 1958- (Hal Leonard Corporation, 2003)
This book contains a lot of music, from musical etudes designed for beginning and intermediate players, to recital material appropriate for intermediate and advanced marimbists. It includes: examples taken from contemporary solo and chamber works, with commentary and performance tips; 50 studies to develop four-mallet technique in a musical way; 18 classic and contemporary solos for recitals, auditions or juries, written by Beethoven, Handel, Chopin, Debussy, Leonard Bernstein, Duke Ellington and others; and helpful guidelines for mallet selection, grip, strokes, tone production, rolls, stickings, phrasing and other important topics.